Rare Post Traumatic Kyphoscoliosis of the Thoracolumbar Spine After Posterior Fusion for Adolescent Idiopathic Scoliosis: A Case Report and Review of the Literature - Calderaro, Cosma (Iowa Orthop J, 2019)
BACKGROUND: Vertebral fracture after posterior arthrodesis and instrumentation for idiopathic scoliosis is a rare occurrence with limited reported cases in the literature. CASE PRESENTATION: A 16-year-old female patient surgically treated for adolescent idiopathic scoliosis with T2-L1 posterior spinal fusion was in a low-energy fall resulting in fracture of L1 and new kyphosis and scoliosis of the thoracolumbar spine at the distal aspect of the fusion. The fracture was initially managed conservatively, however pain persisted and thus she was indicated for extension of the fusion and correction of the post-traumatic kyphosis. CONCLUSIONS: Fractures after posterior spinal fusion for idiopathic scoliosis are rare and evidence for the appropriate management remains limited in the literature. Level of Evidence: V